Role of disulfide bond formation in the folding and assembly of the envelope glycoproteins of a pestivirus. - Branza-Nichita, N; Lazar, C; Durantel, D; Dwek, R; Zitzmann, N (Elsevier, 2002)
Bovine viral diarrhea virus (BVDV) is a pestivirus member of the Flaviviridae family, closely related to, and used as a surrogate model for the hepatitis C virus. Its envelope contains the E1 and E2 glycoproteins, disulfide linked into homo- and heterodimers. In this study, we investigate the role of disulfide bond formation in the folding, assembly, and stability of BVDV glycoproteins. We provide molecular evidence that intact disulfide bonds are critical for the acquirement of a stable conformation of E2 monomers. Forcing the E2 glycoproteins to adopt a reduced conformation either co- or post-translationally before assembly into dimers, determines their misfolding and degradation by proteasome. In contrast, dimerization of E2 glycoproteins results in a conformation resistant to reducing agents and degradation. Furthermore, inhibition of the ER-alpha-mannosidase activity leads to impairment of misfolded E2 degradation, demonstrating the involvement of this enzyme in targeting viral proteins towards proteasomal degradation.